Morphological characterization of the creole backyard chickens of the Subregion sabana department of Sucre (Colombia) - Donicer Montes V (Revista MVZ Córdoba, 2019)
Objective. Characterize morphometric and phaneroptics of the Creole backyard hens from the savanna subregion department of Sucre (Colombia). Materials and methods. 520 adult Creole animals (350 chickens and 170 roosters) were evaluated, in the period 2017-2018, located in 10 localities of the savanna sub-region of the department of Sucre Colombia. The information was collected in a survey format composed of quantitative and qualitative variables. The data obtained were subjected to univariate descriptive analysis, for independent samples. In addition, the analysis of variance technique was used. Comparisons between males and females were made by means of a t-test. The analyses were performed using the statistical package R. Results. The descriptors analyzed showed the superiority of the roosters over the hens (p<0.05). The analysis of variance in the population of females with respect to weight determined that there are significant differences (p<0.05). The morphological and phaneroptic characteristics studied describe a yellow metatarsal bird, with plumage color that combines brown, black, gray and white tones, the morphology and distribution of feathers in most birds is normal characteristic (smooth typical), with a uniform distribution to a length of the body, although specimens with different plumage patterns can be found. Conclusions. A wide variation could be observed among animals from the 10 localities studied. There is evidence of a typological differentiation in relation to the weight and size of the tarsus in the animals evaluated, which can be used as a selection criterion.